State of Repair: Architectures for a Democratic Public - Harvey, Liam (School of Architecture, Planning and Geomatics, 2024)
Power has a multiplicity of manifestations, some overt while others covert. Perhaps it is most visible to the public in the form of architecture. The buildings, precincts, and capitols within which the “powers that be” envelope and exert their authority. These architectures become not only the locus of power exertion, but the symbols by which power and structures of governance are recognized. These structures and symbols present themselves as a part of contemporary society, yet more often than not, they fundamentally exclude the society they claim to stand for and represent. This exclusion is administered by both the physical arrangement and iconography associated with architectures of governance. In the South African context, this contradiction is evinced in the securitisation and separation of colonial state architectures which have been reclaimed as architectures of democracy through sociopolitical revolution. These structures have been stripped of their function as centres of autocratic governance embodied by white supremacy and transformed into the buildings within which a functioning representative democracy is administrated. Although the powers of coloniality and apartheid have been dismantled and destroyed, the symbolism of these divisive regimes has yet to be stripped from our architectures of democracy. This symbolism persists due to the architectural elements of which these buildings are constructed but equally through the fundamentally exclusive nature of the arrangement and spatiality of these buildings. South African society has gone through a complex and hard-fought revolution. It is high time that the spaces and places that represent the leadership of this society - which many fought and died for - come to reflect that revolution, and the South African people as a whole. The architectures of our democracy need not be enclaves of privatised power but rather open and engaging public spaces. Spaces which forthrightly allow the constituents of our democracy a direct connection to the form and administration of our nation. Architecture, as a visual communicator of power, therefore, carries weight for democratic representation of democratic ideals. Thus, this paper investigates how South African architectures of democracy can undergo a state of repair to become truly public and indisputably democratic.